Sustained low‐efficiency dialysis with regional citrate anticoagulation for patients with liver impairment in intensive care unit: A single‐center experience. Issue 2 (3rd August 2020) - Pourcine, Franck; Vong, Ly Van Phach; Chelly, Jonathan; Rollin, Nathalie; Sy, Oumar; Jochmans, Sebastien; Ellrodt, Olivier; Serbource‐Goguel, Jean; Mazerand, Sandie; Michaud, Gael; Nlandu, Yannick; Cirillo, Giulia; et al.
Abstract: Regional citrate anticoagulation (RCA) is a recommended method for extracorporeal circuit anticoagulation during renal replacement therapy (RRT). Increased risk of citrate accumulation by default of hepatic metabolism limits its use in liver failure patients. A Catot /Caion ratio ≥2.5 is established as an indirect control of plasma citrate poisoning. To investigate the safety of RCA in patients with liver impairment during sustained low‐efficiency dialysis (SLED), we conducted a retrospective study of 41 patients with acute or chronic hepatocellular failure requiring RRT between January 2014 and June 2015 in the intensive care unit of the Groupe Hospitalier Sud Ile de France. Sixty‐seven SLED sessions were performed. At admission, 32 (78%) patients had acute liver dysfunction and nine (22%) patients had cirrhosis with a median MELD score of 27 (IQR: 18.8, 42.0). Despite a majority of poor prognosis patients (SAPS‐II (Simplified Acute Physiology Score II) score 71 [IQR: 58; 87]), with acute liver impairment as a part of multi‐organ failure, no dosage of Catot /Caion ratio after SLED sessions exceeded the critical threshold of 2.5. Of the 63 complete sessions, neither dyscalcemia nor major dysnatremia, nor extracorporeal circuit thrombosis were noticed. Observed acid‐base disturbances (16.4%) were not significantly correlated with the Catot /Caion ratio ( P = .2155). In this retrospective study using RCA during intermittent RRT in ICU patients with severe liver dysfunction, we did not observe any citrate accumulation but monitoring of acid‐base status and electrolytes remains necessary to ensure technique safety.